Batik : Design for a Sustainable Environment - Khairul Aidil Azlin, Abd Rahman; Nazlina, Shaari (Universiti Malaysia Sarawak (UNIMAS), 2011)
Sustainability is related to the quality of life in a community. The three components of sustainability are economic, social and environmental systems that make up the community in providing a healthy, productive, meaningful life for all community residents, present and future. The issues of using less, re-use, preservation, conservation, re-manufacturing or rebuilding and recycling all become part of this endless journey. Every process and almost every operation within the batik production such as chanting, dyeing, printing and finishing has environmental aspect that should be consider and which the environmental performance can potentially can be improved. Today, a large proposition of environmental issues in batik industries are related to the use and discharge of water which includes residual dye stuff, toxicity, colour waste, heavy metal contamination and other environmental issues particular to the location of a facility. Furthermore, the highly use of paraffin wax and the emissions of wax fume that generates wide range of harmful chemicals which affected the batik artist’s health. In Batik business and production, through research and development, we have the ability to find new application for alternative method of production and process, materials, for a better world. This presentation will discuss on the key concepts of batik design for sustainable environment within the Malaysian batik industries context.